A comparative ride performance and dynamic analysis of passive and semi-active suspension systems based on different vehicle models - Faris, Waleed Fekry; Ihsan, Sany Izan; Ahmadian, Mehdi (Inderscience Publishers, 2009)
Vehicle models used to evaluate performance and dynamic behaviour are either discrete models, which includes quarter, half, and full car models, or continuous models using finite element modelling. In this work our focus will be on discrete models, which have more popularity with ground vehicle analysts owing to their shorter computational time and lower cost compared with continuous models. In this paper, ride comfort, suspension displacement and road-holding performances are compared for three different models – quarter (Q), half (H) and full (F) car models. In each model, semi-active system controls, namely skyhook, groundhook and hybrid controls, are used along with the conventional passive system. The analysis covers both transient and steady-state responses in the time domain and transmissibility response in the frequency domain. Results show that while the responses give generally the same trend, the simpler model gives significantly higher responses.